PERAN PEKERJA SOSIAL DALAM MENANGANI PERMASALAHAN PESERTA REHABILITASI DI PUSAT REHABILITASI KEMENTERIAN PERTAHANAN INDONESIA - Ifan, Maykel; Khodir, Sihab Abdul (Jurnal Insani, 2021)
This research is a descriptive qualitative research which aims to obtain a description of how the social workers role in handling the problems of rehabilitation participants at the Rehabilitation Center (Pusrehab) of the Indonesian Ministry of Defense. This study determined 3 cases purposively and data collection was carried out by means of observation, interviews, documentation studies. In the rehabilitation implementation process that has been carried out, rehabilitation participants have several social problems is self-acceptance of physical conditions, anxiety of family members regarding conditions experienced by rehabilitation participants, family acceptance of conditions experienced by rehabilitation participants, and difficulty in adjusting to the Pusrehab environment during the rehabilitation process. in handling the problems of rehabilitation participants, social workers do roles like a motivator, counselor, educator, facilitator, advocator, and liaison where the roles very helpful for clients in handling the problems they face. The results of implementing the social workers role in handling the problems of rehabilitation participants shows the changes experienced by the clients.